VARIAÇÃO PRONOMINAL NÓS/A GENTE EM GUARAPUAVA - PR - Deon, Vanessa Aparecida (2015)
The main objective of this research is to analyze the use of nós/a gente in the position of subject in Guarapuava, Paraná. We start with a brief history of linguistics and sociolinguistics, then approach the inclusion of a gente in the pronominal system of Portuguese of Brazil (PB), highlighting some works that present and discuss the grammaticalization process of that pronoun, including: Menon (1995b, 1996), Omena & Braga (1996), Lopes (2003, 2007) and Zilles (2007). In addition, we present the results of some studies on the pronoun variation nós/a gente in Brazil, such as Omena (1998a) e (1998b), Lopes (1998), Menon; Lambach; Landarin (2003) Seara (2000), Borges (2004), Tamanine (2002, 2010) and Franceschini (2011). Based on the results of this research, we selected for our analysis the following linguistic variables: determination of the referent, type of text, tense, verb agreement and tone and three social variables: age, education and gender. The data are from Banco de Dados de Guarapuava, VARLINGUA. In this research, we analyze the speech of 24 informants, collected between the years 2014 and 2015, data were stratified by sex, male and female; age, 25-45 years old and 50 years old or more and schooling, 1-4, 5-8 and 9-12 years of schoolar education. Based on the theoretical assumptions of quantitative sociolinguistics proposed by William Labov (1972, 2008) we analyze the linguistic and social variables listed above to determine which factors influence the use of nós/a gente in our sample. For the statistical analysis we used the GoldvarbX program. The results show that use of the innovative pronoun a gente is starting to exceed the use of canonical pronoun nós in Guarapuava, Paraná. Linguistic factors that favored the use of the innovative pronoun a gente were stressed monosyllables and oxítonos verbs, the uncertainty of the referenced person, the presence of the pronoun, the argumentative text and the present and imperfect tenses. As for the canonical form nós were: paroxytone, the imperfect subjunctive tenses, past tense and unmarked times (gerund and infinitive), the descriptive type of text and the determination of the referent. Concerning the social factors, favored the form a gente speakers of the younger age group, high school, elementary I and women both younger as those in the older age group. In turn favored the canonical form nós: men, older age and the fundamental II. So with this study, we aim to contribute to the description and analysis of Portuguese spoken in Guarapuava and studies of language variation/change in southern Brazil.